Korelasi Kadar Interleukin-6 (IL-6) dan C-Reactive Protein (CRP) Sebelum dan Setelah Aktivitas Fisik pada Pria Umur 18-30 - Karlina Mahardieni; Julian Chendrasari; Miladya Syamsu; John Steward Castellano Lelapari; Julia Aina Syafitri; Suriyani Suriyani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study examined the relationship between Interleukin-6 (IL-6) and C-Reactive Protein (CRP) levels before and immediately after moderate-intensity stair climbing exercise in healthy young adults. Twenty-seven subjects performed a 5-minute stair climbing intervention at 60-80% of their maximum heart rate. IL-6 and CRP levels were measured using ELISA before and immediately after exercise. Pearson correlation analysis showed a very low and non-significant correlation between IL-6 and CRP before exercise (r=−0.004, p = 0.986). After exercise, there was an increase in positive correlation (r=0.277) but it remained statistically non-significant (p = 0.180). These results indicate that physical activity of this duration and intensity does not trigger a strong systemic inflammatory response, and thus IL-6 and CRP levels did not show a significant relationship. Differences in the peak timing of these biomarkers and individual physiological adaptations likely influenced these findings. Further studies with biomarker measurements at multiple time points and varying exercise intensities are needed to better understand the dynamics of IL-6 and CRP responses post-exercise. These findings provide important insight into inflammatory responses to moderate exercise in a healthy young population.